2013
DOI: 10.1039/c3cp51224j
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of CuPc and H2Pc: an experimental and theoretical study

Abstract: Phthalocyanine (H2Pc) and its open-shell copper complex (CuPc) deposited on amorphous gold films have been studied by combining the outcomes of several synchrotron based spectroscopic tools (X-ray photoelectron spectroscopy, UV photoelectron spectroscopy and near-edge X-ray absorption fine structure, NEXAFS, spectroscopy) with those of density functional theory (DFT) calculations. The assignment of experimental evidence has been guided by the results of DFT numerical experiments carried out on isolated molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 80 publications
4
52
0
Order By: Relevance
“…28 Time dependent DFT calculations have been successfully extended to treat also core level excitations in heterocyclic aromatics. 29 On the other hand, the renovated interest in NEXAFS simulations of poly-and heterocyclic aromatics is associated with the study of their interaction with substrates of technological interest. In this context, the relevant parameters for understanding the molecule to substrate interaction from NEXAFS measurements are the atom resolved contributions to the absorption spectra and the electronic structure of the unoccupied molecular orbitals, MOs, in the presence of the core-hole.…”
Section: Introductionmentioning
confidence: 99%
“…28 Time dependent DFT calculations have been successfully extended to treat also core level excitations in heterocyclic aromatics. 29 On the other hand, the renovated interest in NEXAFS simulations of poly-and heterocyclic aromatics is associated with the study of their interaction with substrates of technological interest. In this context, the relevant parameters for understanding the molecule to substrate interaction from NEXAFS measurements are the atom resolved contributions to the absorption spectra and the electronic structure of the unoccupied molecular orbitals, MOs, in the presence of the core-hole.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the relative intensities and relative positions of the X L 2,3 (X = I-III) features satisfactorily agreed with theoretical oscillator strength distributions ( X f). Such a result, combined with estimates of (1) a Cu-S interaction in III more covalent than the Cu-Cl one in I, [9,11] (2) a Cu-N interaction in II less covalent than the Cu-Cl one in I, [11,12] (3) a ligand field in III weaker than that in I [15] and (4) a ligand field in II stronger than that in I [15] represented a successful test of the SO-ZORA TDDFT-TDA method when applied to the modelling of CuII L 2,3 spectra. Interestingly, the composition analysis of the excitations associated with II L 3 revealed that, in addition to 2p 3/2 Ǟ 3d transitions, [18] metal-to-ligand charge-transfer (MLCT) transitions involving low-lying ligand-based π* MOs contribute to the II L 3 intensity and, thus, weaken its believed relationship with the M-L covalency.…”
Section: Complexes ([Cucl 4 ]mentioning
confidence: 79%
“…[8, 12,21] The NEXAFS spectra recorded at the Cu II L 2,3 edges of highly oriented thin films of II and IV are displayed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations